1999
DOI: 10.1046/j.1365-246x.1999.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalizations of power-law distributions applicable to sampled fault-trace lengths: model choice, parameter estimation and caveats

Abstract: Summary It has often been observed that fault‐trace lengths tend to follow a power‐law or Pareto distribution, at least for sufficiently large lengths. A very common method of fitting this type of model to data consists of plotting on log–log axes the number of faults with trace length greater than x against x, and reading off the slope of the resulting approximate straight line. We demonstrate that maximum likelihood is a more efficient and less biased method of estimating the power‐law exponent. A further co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…Because maximum likelihood estimation for the truncated Pareto requires numerical methods, it has been suggested that in some cases with both a minimum and maximum value that the error introduced by assuming that there is no maximum is small enough that it is reasonable to estimate the exponent using the maximum likelihood estimate for the Pareto distribution. Clark et al (1999) suggest this approximation in cases where the maximum value is at least two orders of …”
Section: Complicationsmentioning
confidence: 93%
See 4 more Smart Citations
“…Because maximum likelihood estimation for the truncated Pareto requires numerical methods, it has been suggested that in some cases with both a minimum and maximum value that the error introduced by assuming that there is no maximum is small enough that it is reasonable to estimate the exponent using the maximum likelihood estimate for the Pareto distribution. Clark et al (1999) suggest this approximation in cases where the maximum value is at least two orders of …”
Section: Complicationsmentioning
confidence: 93%
“…There is an error in the MLE solution given by Evans et al (2000) that has been corrected. Note that MLEs are only guaranteed to be minimum variance unbiased estimators in the limit of large n. If n is small, corrections to the MLE are available (Johnson et al 1994, Clark et al 1999, Clauset et al 2007). All solutions assume that a and b are known.…”
Section: Linear Binningmentioning
confidence: 99%
See 3 more Smart Citations